THE INFLUENCE OF JOB TRAINING ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS VARIABLE INTERVENING (Case Study on Employees of the Ministry of Marine Transportation of Serdang Bedagai Regency) - Marbawi; Arilasta Irawan; Siswoyo Adi wijaya (Universitas Efarina, 2023)
In this study, the population was employees of the Ministry of Marine Transportation, Serdang Bedagai Regency, 32 people. Because the target population is less than 100, the sampling technique used is the census method, where the entire population, totaling 32 employees of the Ministry of Marine Transportation, Serdang Bedagai Regency, will be used as the research sample. Research results. the first hypothesis is accepted, meaning that Job Training (X) has a significant effect on Organizational Commitment (Y1). the second hypothesis is accepted, meaning that Job Training (X) has a significant effect on Job Performance (Y2). the third hypothesis is rejected, meaning that Organizational Commitment (Y1) is not an intervening variable that mediates the effect of Job Training (X) on Job Performance (Y2).